Moral constraints on war : principles and cases - Coppieters, Bruno; Ceulemans, Carl; Fotion, N. (Lanham, Lexington Books, 2020)
"This book seeks, in concrete historical terms, to deal with the issue of constraining war on the basis of moral principles as found in Just War Theory. As the book makes clear, this theory has its roots in transcultural experiences, concepts, and principles"--
Includes bibliographical references and index.
Keywords: War -- Moral and ethical aspects; Military history, Modern -- 20th century